KEPEMIMPINAN PROFETIK PADA MASA KHULAFAUR RASYIDIN - Zakki, Mohammad; Fu’adi, Imam; Tanzeh, Ahmad; Kojin (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2023)
The leadership carried out by the khulafaur rashidin is a leadership model that emphasizes the internalization of prophetic values ​​exemplified by the Prophet Muhammad. and previous prophets. The purpose of writing this article is to disseminate leadership values ​​during the Rashidun Khulafaur era so that today's leaders can serve as examples. This study uses the library research method. Then content analysis is carried out as a technique in obtaining authoritative literature data. The results of this study indicate: the prophetic leadership of the caliphs Abu Bakar As Shiddiq, Umar bin Khattab, Uthman bin Affan and Ali bin Abi Talib is generosity in donating property to war fisabilillah, concern and policy for the people, amar makruf and nahi munkar, visionary in paying attention to the future of the people and being brave for the interests and welfare of the people, and the importance of implementing prophetic values ​​in leadership in aspects of government, national, social life, and educational institutions.